Numerical Modeling of Turbulent Bottom Boundary Layer over Rough Bed under Irregular Waves - Rachman, Taufiqur; Suntoyo; Sambodho, Kriyo; Armono, Haryo Dwito; Yusroni, Eko (IPTEK The Journal for Technology and Science, 2025)
A numerical model of turbulent bottom boundary layer over rough bed under irregular waves is reviewed. The turbulence model is based upon Shear Stress Transport (SST) k-omega model. The non-linear governing equations of the boundary layer for each turbulence model were solved by using a Crank-Nicolson type implicit finite-difference scheme. Typically, the main velocity distribution, turbulence kinetic energy and time series of the bottom shear stress are presented. These results are shown to be in generally good agreement with experimental results. The roughness effects in the properties of turbulent bottom boundary layer for irregular waves are also presented with several values of the roughness parameter (am over ks) from am over ks equals 5 to am over ks equals 3122. The roughness effect tends to decrease the main velocity distribution and to increase the turbulent kinetic energy in the inner boundary layer, whereas in the outer boundary layer, the roughness alters the mean velocity distribution and the turbulent kinetic energy is relatively unaffected. The effect of bed roughness on the bottom shear stress under irregular waves is found that the higher roughness elements increase the magnitude of bottom shear stress along wave cycle. Furthermore, the bottom shear stress under irregular waves is examined with the existing calculation method and the newly proposed method.